Answer:
Explanation:
Let the consecutive even integers be 2n and 2n+2.
lesser integer = 2n
Greater integer = 2n+2
If twice the lesser of two integers is 4 less than two times the greater integer, this is expressed mathematically as;
2(less integer) = 2(greater integer) - 4
Substituting the given integers;
2(2n) = 2(2n+2)-4
2(2n) = 2[(2n+2)-2]
2n = 2n+2-2
2n = 2n
2 = 2
This two values cancels out and become 0 = 0. This equality shows that it is an identity pair and it is true for all even integers.